Exploring limit behaviour of non-quadratic terms via H-measures. Application to small amplitude homogenisation. Issue 16 (10th December 2017) - Lazar, Martin
Abstract : A method is developed for analysing asymptotic behaviour of terms involving an arbitrary integer order powers of functions by means of H-measures. It is applied to the small amplitude homogenisation problem for a stationary diffusion equation, in which coefficients are assumed to be analytic perturbations of a constant, enabling formulæ for higher order correction terms in a general, non-periodic setting. Explicit expressions in terms of Fourier coefficients are obtained under periodicity assumption. The method allows of its generalisation and application to the corresponding non-stationary equation, as well as to some other small amplitude homogenisation problems.